Energy Harvesting Untethered Soft Electronic Devices (Adv. Healthcare Mater. 17/2021). Issue 17 (8th September 2021) - Kim, Kyun Kyu; Choi, Joonhwa; Ko, Seung Hwan
Abstract : Human–Machine Interfaces In article number 2002286, Seung Hwan Ko and co‐workers review the cutting edge of wearable devices. Recent development of untethered devices consists of a range of cutting‐edge technologies such as electromagnetic, triboelectric, and thermoelectric energy harvesting. Recent advances in bio‐fuel‐based electronics show numerous solutions to the remaining practical issues of continuous measurement without an external power source. Key advancements in untethered devices in various power sources are introduced with their principles and working mechanisms.